2010
DOI: 10.1097/psy.0b013e3181d96550
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcome in Patients With Psychogenic Nonepileptic Seizures

Abstract: These results demonstrate the need for earlier diagnosis of PNES and comorbidities and highlight the need for diagnostic and therapeutic approaches that combine neurological and psychiatric perspectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 43 publications
8
74
1
4
Order By: Relevance
“…Firstly, the commonly lengthy process of reaching a diagnosis of PNES can be a lot more expensive, when compared to the diagnostic process of other chronic conditions [11]. Financially these patients are often confronted with a delay in confirming a diagnosis of PNES due to numerous doctors' visits, inappropriate treatment and medication that changes constantly [4,5,10,17]. In addition, hospitalizations in speciality units, extensive testing and monitoring with specialised equipment such as video-EEG can be expensive [4,11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the commonly lengthy process of reaching a diagnosis of PNES can be a lot more expensive, when compared to the diagnostic process of other chronic conditions [11]. Financially these patients are often confronted with a delay in confirming a diagnosis of PNES due to numerous doctors' visits, inappropriate treatment and medication that changes constantly [4,5,10,17]. In addition, hospitalizations in speciality units, extensive testing and monitoring with specialised equipment such as video-EEG can be expensive [4,11,12].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many healthcare providers do not have the expertise to diagnose and treat PNES and subsequently, patients with PNES may find themselves on the border between neurology and psychiatry with neither of these professions prepared to take responsibility for treating this complex condition [1]. Studies indicate that the average period between seizure manifestation and correct 2 diagnosis of PNES is about seven years [10]. During the diagnostic process patients are often confronted with extensive and expensive testing [11] as well as a lack of understanding of this condition from healthcare providers [1,5,8,12].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with NES were classified into those who had psychogenic NES (PNES) and those who did not. PNES were defined as typical episodes with no corresponding epileptiform activity on the EEG during the episodes or episodes that were secondary to a suspected conversion or dissociative mechanism [21]. All episodes secondary to a medical cause or other psychiatric conditions such as panic attacks were excluded.…”
Section: Nonepileptic Seizuresmentioning
confidence: 99%
“…Patients with nonepileptiform seizures (NES), particularly psychogenic nonepileptic seizures (PNES), constitute a large proportion of patients assessed in epilepsy services [20,21], and suffer significant medical and psychiatric morbidity, a poor quality of life, and a poor functional outcome [22,23]. Patients with NES often do not differ in their level of cognitive impairment from patients with proven epilepsy [24], with both groups generally performing worse on tests of overall cognitive function than the healthy population [25].…”
Section: Introductionmentioning
confidence: 99%
“…Research of patients with PNES diagnosed with video EEG has consistently shown that only about 10% of patients have concurrent epileptic seizures (Jones 2010;McKenzie 2010). It is important to stress that even in cases where comorbidity is confirmed, the clinical picture is generally of frequent PNES in the context of underlying well-controlled epilepsy (Duncan 2008).…”
Section: Declaration Of Interestmentioning
confidence: 99%